2022
DOI: 10.1017/s1092852922000037
|View full text |Cite
|
Sign up to set email alerts
|

What misdiagnoses do women with autism spectrum disorder receive in the DSM-5?

Abstract: Recently increasing literature is focusing on sex differences in the manifestations of Autism spectrum disorder (ASD), highlighting the presence of several possible female-specific features of this condition. 1 Some authors also pointed out that ASD diagnostic criteria would be tailored on the typical male presentations of the disorder, leading to an under-recognition of ASD among females. Subsequently ASD females, in particular those without language or intellectual impairment, would likely receive other kind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 6 publications
2
26
0
Order By: Relevance
“…22,40,41,43,[45][46][47][48][49][50] In addition, subjects in the autism spectrum, even when having experienced major traumatic events, may not be able to properly report it due to their difficulties in processing and communicating life experiences. 5,7,31,48 According to our findings, autism spectrum subjects reported a strikingly higher rate of PTSD when compared with the HC group from our study (30% versus 0%). The reported prevalence was higher also when compared with ranges reported in the general population, which are around 3-4%.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…22,40,41,43,[45][46][47][48][49][50] In addition, subjects in the autism spectrum, even when having experienced major traumatic events, may not be able to properly report it due to their difficulties in processing and communicating life experiences. 5,7,31,48 According to our findings, autism spectrum subjects reported a strikingly higher rate of PTSD when compared with the HC group from our study (30% versus 0%). The reported prevalence was higher also when compared with ranges reported in the general population, which are around 3-4%.…”
Section: Discussionsupporting
confidence: 58%
“…As a consequence, autism spectrum among females may remain masked by other diagnosis, spanning from eating disorder to social anxiety, borderline personality disorders, and trauma and stress-related disorders. 7,14,[57][58][59] Other studies also stressed that individuals with AT after traumatic exposure may more likely develop mood disorders, enhanced by PTSD symptoms and altered circadian rhythms symptoms. This hypothesis is in line with previous researches that highlighted a role of trauma/stress-related symptoms in the relationship between autism spectrum and increased suicidal risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the validation study [1], the AdAS Spectrum questionnaire demonstrated an excellent reliability and a strong convergent validity with other scales employed in this field, such as the Autism-Spectrum Quotient Test [22] and the e Ritvo Autism and Asperger Diagnostic Scale 14-item version [23]. The AdAS Spectrum has been used, in recent years, within numerous studies focusing on the autism spectrum both in clinical and in nonclinical settings [24][25][26][27][28][29][30][31][32][33].…”
Section: The Adult Autism Subthreshold Spectrummentioning
confidence: 99%
“…Reaching a shared consensus on the theoretical conceptualization of social camouflaging—as a feature specific to, but possibly not exclusive of, people on the autism spectrum—should be considered as one of the next goals to aim for. Such a model should reflect the actual camouflaging experiences of people with ASD, taking into account the specific female presentations that often remain undetected due to the actual gender biased conceptualization of ASD [ 43 , 46 , 64 , 72 , 82 , 88 , 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%